Strategic Internal Communication in Organizational Change: A Narrative Review of Practices and Barriers - Adnan, Iis Zilfah; Suratmoko, Bayu (Indonesian Scientific Publication, 2024)
This narrative review explores the strategic role of internal communication in driving successful organizational change. The review aims to identify effective communication techniques, assess employee engagement dynamics, evaluate the integration of digital tools, and examine cross-cultural and sectoral differences. A structured review methodology was employed using literature from Scopus, Web of Science, JSTOR, and Google Scholar. Keywords included